Peran Pola Asuh Orang Tua Dalam Mendidik Anak Diera Digital Di Desa Kotawaringin - Linda, Marlinda (IJoCE: Indonesian Journal of Counseling and Education, 2025)
The aim of this research is to determine parents' parenting patterns in educating children in the era of digital technology in Kotawaringin Village. Technological progress is inevitable. In today's digital era, technology has been completely assimilated into our daily lives. The lives of young children today have changed in several ways as a result of this. The digital era offers advantages and disadvantages. Technological developments are increasingly rapid in the digital age today, causing the values that are born, both positive and negative also experience a tremendous surprise for humans. This research uses a descriptive approach with quantitative methods, namely describing parents' parenting patterns in educating children in the era of digital technology in Kotawaringin Village. The population in this study was all parents of children in Kotawaringin Village, totaling 73 people, and the sample in this study was all parents (fathers and mothers) of children in Kotawaringin Village, totaling 146 people. This research was carried out from November 13 to November 29 2024. The research instrument was a multiple choice questionnaire. The data collection technique is in the form of a questionnaire or questionnaire. The results of the research state that parents in Kotawaringin Village use authoritarian parenting patterns based on the percentage of parents' answers as a whole, namely 59% authoritarian, 15% democratic parenting, 26% permissive parenting in the era of digital technology.